2023
DOI: 10.3390/su15032210
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Performance-Based Environmental Impacts of Substituting Soybean Meal with Rapeseed Meal in the Rye-Based Diet of Weaned Pigs

Abstract: Due to its favorable properties, soybean meal (SBM) is used especially in young growing animals. In terms of sustainability, there are various efforts to reduce the amounts of SBM in compound feeds and to increase the use of regional protein sources. This paper focuses on the effects of a partial to total substitution of SBM by regionally produced rapeseed meal (RSM) in different piglet diets regarding 10 important factors having an impact on the environment. Four diets, characterized by different shares (%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Rye is also a valuable cereal in terms of sustainability. It has been shown that a compound feed with high proportions of rye in combination with regional protein sources leads to a lower carbon footprint while maintaining the same performance [11]. Despite its similarity to wheat feeding, a rye-rich diet has an influence on the physicochemical properties of the digesta of pigs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Rye is also a valuable cereal in terms of sustainability. It has been shown that a compound feed with high proportions of rye in combination with regional protein sources leads to a lower carbon footprint while maintaining the same performance [11]. Despite its similarity to wheat feeding, a rye-rich diet has an influence on the physicochemical properties of the digesta of pigs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration the reduction of N in the NC diet, as well as the positive effects found when the probiotic was supplemented in the NC diet, replacing SBM with RSM could potentially be a viable cheaper and eco-friendly alternative to imported SBM protein sources in pig diets. Furthermore, the use of RSM instead of SBM in pig diets could be a viable tool for markedly reducing these animals' negative impact on climate change [21].…”
Section: Discussionmentioning
confidence: 99%
“…Replacing soybean meal (SBM) with protein sources from European agricultural systems, such as as rapeseed meal (RSM), could potentially be a viable cheaper and ecofriendly alternative to imported SBM protein source in pig diets and could contribute to more sustainable pork production [20]. Furthermore, the use of RSM instead of SBM in pig diets could be a viable tool for markedly reducing the negative impact on climate change [21]. Previous studies have shown that SBM can be partially replaced with RSM without affecting the performance of growing-finishing pigs [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Among other things, this is why cultivation generates a relatively low CO 2 footprint (7). Thus, an old and traditional feedstuff is experiencing growing interest (8)(9)(10)(11)(12)(13)(14)(15). Generally, wheat and rye are characterized by different amounts of starch and crude fiber (3), moreover crude protein levels of wheat are 17-33% higher than those of rye (3,16).…”
Section: Introductionmentioning
confidence: 99%